ANALISIS AGRIBISNIS SAPI POTONG DI KABUPATEN SIAK PROVINSI RIAU - Nurkhadijah Nurkhadijah; Syaiful Hadi; Evy Maharani (DINAMIKA PERTANIAN, 2017)
The study aimed to analyze the influence of each subsystem on the income of farmers and between each sub-system is itself on beef cattle farms in Siak. The study was conducted in 4 (four) districts in Siak District of Kerinci Kanan, Lubuk Dalam, Dayun and Koto Gasib using simple random sample selection method. Total sample in this study were 100 breeders. Data were analyzed by scoring and path analysis (path analysis). Path analysis results indicate that the up-stream subsystem to the farmer’s income. The influence between the subsystem they are as follows: Subsystems supporting institutions affecting the entire subsystem of agribusiness, marketing subsystem affect up-stream subsystem, on-farm subsystem, and down-stream subsystem agribusiness, up-stream subsystem to the on-farm agribusiness, on-farm subsystem to down-stream agribusiness. The conclusion of the research indicated that the implementation of beef cattle subsystem agribusiness had an adequate index and give positive effect to the farmer’s income.